Fifty years of progress in wildland fire modelling: from empirical to fully physical CFD models - Morvan, Dominique; Accary, Gilbert; Meradji, Sofiane; Frangieh, Nicolas (Comptes Rendus. Mécanique)
The aim of this short review is to present the progress made in wildland fire modelling during the last 50 years and the intellectual track followed by wildland fires models, from fully empirical models in the 60s, to semi-empirical ones in the 70s, to fully physical models at the end of the 90s. During the last period, the large diffusion of HPC methods substantially contributed to the development of multiphase formulations applied to wildland fire modelling. Many studies have particularly focused on the effects of various parameters (vegetation, topography, atmosphere) affecting the behaviour of a fire front propagating through a forest fuel layer.